PENGGUNAAN INTERNET DAN KONTROL DIRI (SELF CONTROL) PESERTA DIDIK SMA MUHAMMADIYAH 1 PEKANBARU - Alvida Hepbri Yusa; Tri Umari; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Technological Developement can have an impact of internet usage of individual, so self control have to needed. Self control is how a person control and do his/her self control so that it can be accepted as positive consequence. If an individual has good self control, she/he has also be able to use the internet well. Based of fenomena that occure at SMA Muhammadiyah 1 Pekanbaru, school advocate student to acces the internet at lesson time, but not a little students can control his/her self to used internet as it should be. The purpose of this research is to find out one’s internet usage and his/her self control. This research is used 112 samples from all of student who used internet. The research used descriptive method with quantitatif approach. The istrument of research used questionaire with likert scale. Technique collection data is used a simple random sampling. The result of the research are students used internet every day more than three hours in one day, internet many used to find an information and many used at free time. The level of internet used generally is located at medium category and the level of self control generally at good category, it means student can control his/her self in an internet usage. For that, students are expected can to stay keep their internet usage and their self control, to parents teacher and counsellor are expected to more pay attention for students developement.Keyword : Internet, Self Control, Student